How transport modes, the built and natural environments, and activities influence mood: A GPS smartphone app study. (December 2019) - Glasgow, Trevin E.; Le, Huyen T.K.; Scott Geller, E.; Fan, Yingling; Hankey, Steve
Abstract: Transportation-related mood studies relying on retrospective surveys incur recall bias, given the transient state of mood. Additionally, previous research in this domain has been limited to a single time-point measurement of mood, making it impossible to evaluate within-person variation. This study applied experience sampling methodology (ESM) to explore how mood during travel relates to transport mode, activities, and the built and natural environments. A smartphone application was employed to overcome the limitations of prior studies in this domain. Participants tracked their trips for at least one week and completed mood surveys after each trip. After accounting for within-person variation, active travel correlated with more positive mood than motorized travel, and mood was more positive when individuals talked to others during their trips. However, mood was more negative when completing errand trips as compared to other types of trips. Mood was lower when individuals traveled through places with a higher Walk Score®, but higher when individuals traveled through natural environments. All participants felt less safe when bicycling. This field study was one of the first to consider within-person differences in mood during travel as a function of various environmental and transportation characteristics. The research demonstrated how information on mood could be used to promote sustainable transportation (e.g., walking, bicycling), as well as how urban transportation infrastructure could be designed to enhance mental well-being. Highlights: Experience sampling methodology used a phone app to measure mood during travel. Mood differed as a function of exposure to various built and natural environments. Positive mood was higher for pedestrians and for bicyclists. Interpersonal conversation during trips was associated with more positive mood. Errand trips were associated with more negative mood compared to other trips.